Need Analysis to Develop Electronic Student Worksheet Based on Problem Based Learning to Improve Students' Problem-Solving Skills - Winarsih, Puput; Desnita (Journal of Innovative Physics Teaching, 2025)
Twenty first century learning demands that students possess critical thinking, creativity, and problem-solving skills. However, physics education in Indonesia particularly in the topic of renewable energy is still conducted using conventional methods and lacks active student involvement. In fact, this topic has the potential to foster higher-order thinking skills. This study aims to analyze the need for the development of a Problem-Based Learning (PBL) based Electronic Student Worksheet (E-SWS) to improve students' problem-solving abilities. A needs analysis was conducted to gain a comprehensive understanding of the learning conditions, challenges encountered, and appropriate teaching material specifications. The method used was descriptive with a mixed quantitative and qualitative approach, utilizing questionnaires and interviews. The research findings indicate that: (1) students feel bored and unmotivated when learning physics; (2) the learning models and media used are not optimal in enhancing understanding and thinking skills; (3) the teaching materials, particularly the student worksheets, are not yet technology-based and the content is inadequate; and (4) students’ problem-solving abilities are still low, reaching only 38.9%. These findings highlight the need to develop a PBL-based E-SWS as a solution to enhance students’ learning interest and problem-solving skills in the digital era